MENGGALI POTENSI PEMANFAATAN LAHAN MARGINAL MENJADI LAHAN PRODUKTIF DALAM RANGKA MEMPERTAHANKAN KETERSEDIAAN PANGAN DI MASA MENDATANG - Eri Yusnita Ervianti; Nova Reniati; Tirta Yoga (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2024)
Marginal land is a critical land that is less promising. This study aims to identify and analyze the potential of marginal land to anticipate future food availability and to review the constraints faced by marginal land. The methods used is literature study and comparative study. A literature study was conducted to obtain a theoretical basis on the standard of agricultural research centers on marginal lands, while a comparative study was conducted to obtain an overview of agricultural research on marginal lands in Indonesia. The results showed that marginal land had various cultivation potentials such as rice, corn, oil palm, sweet potatoes, and peanuts. The potential of the livestock sector and the tourism sector can also be a potential choice for exploiting the potential of marginal land. The potential for marginal land in the future is expected to be used as a more productive land as an alternative in preparing food availability in the future. So that food and ecosystem stability is maintained. Socio-economic aspects that are considered in the management of marginal land include agro-economy, production, marketing, and institutions. Meanwhile, the constraints on the utilization of marginal land are, among others, prone to high erosion rates, low fertility levels, limited capital, limited facilities and infrastructure, and high rates of crop failure.